The role of the financial sector in enhancing economic growth in Lao PDR - Kristina Spantig (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2014)
In recent years the Lao PDR's financial sector developed fast in terms of financial depth, intermediation and distribution. A developed financial sector is the basis for dynamic economic growth. Yet, unsustainable financial liberalization and growth poses risks to financial sector stability. The study scrutinizes the role of the financial sector in enhancing economic gworth in Lao PDR and aims to answer the question of adequate financial sector supervision with respect to the economy's development. It is argued that only a prudentially supervised financial sector can enhance the economic growth performance of Lao PDR in the medium and long run.
Keywords: G01; G32; O11; O16; O49; 330; finance-growth nexus; financial sector development; supervision